Effect and safety of antithrombotic therapies for secondary prevention after acute coronary syndrome: a network meta-analysis - Mo FR; Li J; Yan YL; Wu WF; Lai SY (Dove Medical Press, 2018)
Fanrui Mo,1 Juan Li,2 Yuluan Yan,2 Weifeng Wu,1 Shayi Lai2 1Department of Cardiology, The First Affiliated Hospital of Guangxi Medical University, Nanning, China; 2Department of Cardiology, The Fourth Affiliated Hospital of Guangxi Medical University, Liuzhou, China Background: Dual antiplatelet therapy is a standard protocol for secondary prevention after acute coronary syndrome, but despite a variety of new dual antithrombotic strategies, there is a dearth of studies evaluating the effects and safety of some popular therapies. This study used a network meta-analysis to compare the efficacy and safety of all available antithrombotic therapies. Methods: PubMed, MEDLINE, and Cochrane library databases were searched for randomized controlled trials, published up to July 1, 2017, that evaluated the efficacy of antithrombotic therapy in acute coronary syndrome treatment. The primary endpoints were clinically significant bleeding and major bleeding and secondary endpoints were major cardiovascular events, all-cause deaths, cardiac deaths, and myocardial infarction. Results: Compared with treatment with aspirin + new P2Y12 inhibitor, treatment with aspirin + new P2Y12 inhibitor converted to clopidogrel clinically reduced the risk of major cardiovascular events or significant bleeding (OR: 0.30, 95% credibility interval: 0.12–0.75). Both myocardial infarction risk (OR: 0.82, 95% credibility interval: 0.62–1.09) and major bleeding risk (OR: 0.18, 95% credibility interval: 0.01–1.68) were not significantly different between treatment regimens. There were no significant differences in major cardiovascular events, all-cause deaths, cardiac deaths, myocardial infarction, clinically significant bleeding, and major bleeding risk with rivaroxaban + new P2Y12 inhibitor therapy when compared with aspirin + new P2Y12 inhibitor. Compared with aspirin + clopidogrel, the conversion therapy further reduced the risk of myocardial infarction (OR: 1.81, 95%, credibility interval: 1.01–1.34) without an increased clinical risk of significant bleeding (OR: 0.41, 95%, credibility interval: 0.15–1.07). Treatment with aspirin + new P2Y12 inhibitors reduced all-cause deaths (OR: 0.91, 95% credibility interval: 0.84–0.98) and cardiac death risk (OR: 0.86, 95% credibility interval: 0.79–0.93). Conclusion: We concluded the following from our study: 1) an aspirin + new P2Y12 inhibitor/clopidogrel conversion treatment strategy was not inferior to aspirin + new P2Y12 inhibitor; 2) compared with aspirin + clopidogrel, the conversion strategy may further reduce the risk of myocardial infarction without increasing the risk of bleeding; and 3) compared with aspirin + clopidogrel, treatment with aspirin + new P2Y12 inhibitors may result in reduced risk of death. Keywords: antithrombotic therapies, secondary prevention, acute coronary syndrome, network meta-analysis